COVID-19 and Avoiding Ibuprofen. How Good Is the Evidence?. (July 2020) - Kutti Sridharan, Gurusaravanan; Kotagiri, Rajesh; Chandiramani, Vijay H.; Mohan, Babu P.; Vegunta, Rathnamitreyee; Vegunta, Radhakrishna; Rokkam, Venkata R. P.
Abstract : Ibuprofen is an over-the-counter medication that is used widely for the treatment of pain and fever during COVID-19 pandemic. A concern was raised regarding the safety of ibuprofen use because of its role in increasing ACE2 levels within the Renin–Angiotensin–Aldosterone system. ACE2 is the coreceptor for the entry of SARS-CoV-2 into cells, and so, a potential increased risk of contracting COVID-19 disease and/or worsening of COVID-19 infection was feared with ibuprofen use. However, available data from limited studies show administration of recombinant ACE2 improves lung damage caused by respiratory viruses, suggesting ibuprofen use may be beneficial in COVID-19 disease. At this time, there is no supporting evidence to discourage the use of ibuprofen.